2017
DOI: 10.3390/polym9040135
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Approach for Fabrication of Core-Shell Magnetic Molecularly Imprinted Nanospheres towards Hypericin

Abstract: By taking advantage of the self-polymerization of dopamine on the surface of magnetic nanospheres in weak alkaline Tris-HCl buffer solution, a facile approach was established to fabricate core-shell magnetic molecularly imprinted nanospheres towards hypericin (Fe 3 O 4 @PDA/Hyp NSs), via a surface molecular imprinting technique. The Fe 3 O 4 @PDA/Hyp NSs were characterized by FTIR, TEM, DLS, and BET methods, respectively. The reaction conditions for adsorption capacity and selectivity towards hypericin were op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…In both scenarios, the characteristic absorption of C=O from 5 at 1735 cm −1 , 2103, 3274, and 2570 cm −1 ascribed to the absorptions of C≡C, C–H in alkynyl groups on 1 [ 30 ] and S–H on 5 , respectively were not observed on the spectra of the polymers (MIP–NSHs and NIP–NSs). Moreover, the absorption band of C–O on hypericin at 1230 cm −1 [ 38 ] was found on the spectrum of MIP–NSHs. The results indicated that the click reaction of thiol-yne successfully occurred in both cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both scenarios, the characteristic absorption of C=O from 5 at 1735 cm −1 , 2103, 3274, and 2570 cm −1 ascribed to the absorptions of C≡C, C–H in alkynyl groups on 1 [ 30 ] and S–H on 5 , respectively were not observed on the spectra of the polymers (MIP–NSHs and NIP–NSs). Moreover, the absorption band of C–O on hypericin at 1230 cm −1 [ 38 ] was found on the spectrum of MIP–NSHs. The results indicated that the click reaction of thiol-yne successfully occurred in both cases.…”
Section: Resultsmentioning
confidence: 99%
“…The binding selectivity of MIP–NSHs and NIP–NSs was evaluated by following the method reported [ 38 ]. Briefly, 5 mg of the MIP–NSHs or NIP–NSs were incubated respectively with 5 mL of hypericin, protohypericin, and emodin solution (12.5 μM in acetone) at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…However, where the fingerprint of the PDA results unambiguous is in the 1700-1300 cm −1 energy range: well defined bands are observed at ca. 1627, 1552, 1414, and 1345 cm −1 assigned to υ(C=O), υ(C=N), υ(NH 3 ), and δ(C-N-C) vibration modes, respectively [34,35]. Once the presence and content of the catalyst components has been determined, we will analyze their distribution at the nano-scale combining HRTEM, HAADF, STEM-mapping, XRD, and adsorption desorption N 2 isotherms.…”
Section: Catalysts Characterizationmentioning
confidence: 99%
“…To this day, few reports on hypericin-MIPs have been published in the literature. For instance, Pei et al prepared molecularly imprinted nanospheres, via click reactions (azide-alkyne and thiol-yne) and surface imprinting techniques, using core-shell magnetic MIP [21,22].…”
Section: Molecularly Imprinted Polymer Pearls Obtained By Phase Invermentioning
confidence: 99%